ORAL REHABILITATION OF A GERIATRIC PATIENT WITH VELOPHARYNGEAL INSUFFICIENCY: A CASE REPORT - Khan, Afeera; Akhtar, Afsheen; Saleem, Tayyaba (Journal of Postgraduate Medical Institute, 2024)
The defect in Velopharyngeal (VP) valve leads to problems in speech and swallowing. Such defects can be managed either by surgical means or palatal obturator. Fabrication of obturator in edentulous patients present many challenges like lack of retention and support leading to functional compromise of prosthesis. This case report describes rehabilitation of a geriatric patient who was surgically treated for mucoepidermoid carcinoma of hard and soft palate. After surgery, patient complained of nasal regurgitation of food and hypernasal speech. A wrought wire in zigzag shape was used to attach the pharyngeal obturator to maxillary overdenture for better retention and support of prosthesis.